2011
DOI: 10.5539/ijef.v3n1p208
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Elasticities of Electricity Consumption for Rural and Urban Areas in Malaysia: A Non-linear Approach

Abstract: This paper investigates and estimates the price and income elasticity of electricity consumption and then compares the level of sensitivity of demand for electricity in the rural and urban areas in Malaysia. The non linear model was employed to estimate the elasticity of electricity consumption. The electricity demand has been estimated as a function of tariff, real GDP, gas price and population in the rural and urban population. The gas price has been used as a proxy to measure the level of sensitivity goods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…It shows that all variables are substantially stationary [I (1)] at 1% except for LD. The stationarity results are consistent with most of previous studies that employed financial and macroeconomics variables that claimed these variables are nonstationary at level, but they would become stationary after the first or second difference (Bekhet & Mugableh, 2012;Bekhet & Othman, 2011). //doi.org/10.15405/epsbs.2020.12.05.55 Corresponding Author: Nor Salwati Othman Selection and peer-review under…”
Section: Resultssupporting
confidence: 87%
“…It shows that all variables are substantially stationary [I (1)] at 1% except for LD. The stationarity results are consistent with most of previous studies that employed financial and macroeconomics variables that claimed these variables are nonstationary at level, but they would become stationary after the first or second difference (Bekhet & Mugableh, 2012;Bekhet & Othman, 2011). //doi.org/10.15405/epsbs.2020.12.05.55 Corresponding Author: Nor Salwati Othman Selection and peer-review under…”
Section: Resultssupporting
confidence: 87%
“…8; The second strand deals with the relationship between energy, FDI and GDP. Bekhet and Othman (2010) Based on the previous findings, this study hypothesized that there is a long run relationship between export, FDI and electricity consumption in Malaysia. In particular, the positive relationship will exist between EC and innovative economic activities if the scale effect exceed the technical effect.…”
Section: Past Studiesmentioning
confidence: 99%
“…All variables are expressed in logarithmic form in order to obtain more stationary behavior (Bekhet & Othman, 2010), and reduce the possibility of heteroscadasticity and autocorrelation to be exist. The detail and sources of variables used in this study are shown in table 2.…”
Section: Data and Variablesmentioning
confidence: 99%
“…Real gross domestic product (GDP) serves as a proxy for real disposable income (Amusa et al, 2009;Asafu-Adjaye, 2000;Athukorala and Wilson, 2010). Price indexes are used as proxy for price of electricity (gross rent, fuel and power) and price of electric appliances (furniture, furnishings and household equipment and operation) (Bekhet and Othman, 2011a;Chandran et al, 2010). The data on FDI, given as a percentage of GDP, are converted into real FDI by multiplying by real GDP.…”
Section: Data Sources and Methodologiesmentioning
confidence: 99%